Identifying Key Research Objectives to Make European Forests Greener for Bats - Russo, Danilo; Billington, Geoff; Bontadina, Fabio; Dekker, Jasja; Dietz, Markus; Gazaryan, Suren; Jones, Gareth; Meschede, Angelika; Rebelo, Hugo; Reiter, Guido; Ruczyński, Ireneusz; Tillon, Laurent; et al. (Frontiers in Ecology and Evolution, 2016)
Bats are a biodiverse mammal order providing key ecosystem services such as pest suppression, pollination and seed dispersal. Bats are also very sensitive to human actions, and significant declines in many bat populations have been recorded consequently. Many bat species find crucial roosting and foraging opportunities in European forests. Such forests have historically been exploited by humans and are still influenced by harvesting. One of the consequences of this pressure is the loss of key habitat resources, often making forests inhospitable to bats. Despite the legal protection granted to bats across Europe, the impacts of forestry on bats are still often neglected. Because forest exploitation influences forest structure at several spatial scales, economically viable forestry could become more sustainable and even favour bats. We highlight that a positive future for bat conservation that simultaneously benefits forestry is foreseeable, although more applied research is needed to develop sound management. Key future research topics include the detection of factors influencing the carrying capacity of forests, and determining the impacts of forest management and the economic importance of bats in forests. Predictive tools to inform forest managers are much needed, together with greater synergies between forest managers and bat conservationists.